Synthesis, structure, and rearrangement of 1,3-Dibora(5)radialenes - Enders, Markus; Krämer, Albrecht; Pritzkow, Hans; Siebert, Walter (Angewandte Chemie. International edition, 1991)
The new 1,3-bis(dimethylamino) derivative 1 is isoelectronic with decamethyl[5]radialene. The analogous 1,3-dimethyl compound 2 undergoes slow 1,5-sigmatropic H shift to give a 1,3-diborafulvene. This process is faster in the reaction with [Mo(CO)6], whereby the product is the [Mo(CO)4] complex 3.
Gesehen am 30.11.2022